Penataan Prasarana Kawasan Permukiman Tepian Kanal Jongaya Berbasis Masyarakat - Fredy Andi Lolo; Mimi Arifin; Wiwik Wahidah Osman (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
The residential area located on the outskirts of the Jongaya Canal is one of the causes of pollution in the abiotic environment, such as the buildup of high-quality waste that has an impact on the contamination of Losari Beach as one of the landmarks of Makassar City. The purpose of this study is 1) to identify the community towards the condition of the edge of the Jongaya Canal 2) to identify people's preferences towards the settlements on the banks of the Jongaya Canal in Bontorannu Village, Mariso District and Maccini Sombala Sub-District, Tamalate Sub-District, Makassar City and 3) Arrange the directions for the Jongaya Canal slum in Kelurahan Bontorannu, Mariso District and Maccini Sombala Sub-District, Tamalate District, Makassar City, are community-based. The analytical method used in this study is descriptive qualitative and quantitative, and spatial analysis. The results of the study show that settlement development responsible for the community itself increases the potential and participation of the community needs to be developed in the development of existing settlements. In addition, the amount is a contribution in the construction of houses, housing and residential environments that are renewed renovation, renovation, rejuvenation of residential neighborhoods and housing development. As for the direction of this study is the construction of infrastructure networks at the research site. The research proposal is stimuli available to the public stimulation this is what needs to be engineered so that society and the environment must be as expected.